PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI pada Tahun 2010-2013) - Kholifah Triningrum, 11.05.52.0087; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2015)
The sample in this research are manufacturing companies listed in Indonesia Stock Exchange during the years 2010 - 2013 and obtained as many as 53 companies fit the criteria of which is in charge with purposive sampling technique. The analysis technique used is logistic regression. The results showed that managerial ownership variable effect on earnings management. Meanwhile, institutional ownership, reputation audit and frequency of earnings management has no effect on earnings management. Keywords: Managerial Ownership, Institutional Ownership, Reputation Audit, The Frequency of Audit Committee Meetings and Earnings Management